Exchangeable Trace Ions in Lake Erie Sediments - Witteman, J.P. (My University, 1971)
Sediment from Lake Erie was leached with distilled water to obtain exchangeable trace elements. Sediment factors considered were organic carbon, pH of leaching and clay composition. Organic carbon decreases with depth in the sediment. The pH remained nearly constant (6.2 - 9.2). Typical concentrations of leached metals are 5 - N50 ppb Zn, 15 - 75 ppb Cd, 6 - 200 ppb Cu, 8 - 34 ppb Cr, and 17 - 100 ppb Ni. The ratio of clay minerals, Kaolinite : Illite : Chlorite = 50 : 40 : 10. In all cores exchangeable trace ions highly correlated with organic carbon and both decrease with depth in the sediment .
Title: Exchangeable Trace Ions in Lake Erie Sediments, Author: J.P. Witteman, Location: Thode